2011
DOI: 10.1111/j.1365-2672.2011.05137.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of ceramic-based cell immobilization to produce 1,3-propanediol from biodiesel-derived waste glycerol with Klebsiella pneumoniae

Abstract: Aims:  The feasibility of the continuous production of a valuable bioplastic raw material, namely 1,3‐propanediol (1,3‐PDO) from biodiesel by‐product glycerol, using immobilized cells was investigated. In addition, the effect of hydraulic retention time (HRT) was also analysed. Methods and Results:  Ceramic balls and ceramic rings were used for the immobilization of a locally isolated strain; Klebsiella pneumoniae (GenBank no. ). HRT of 1 h is the best one in terms of volumetric production rate (g 1,3‐PDO l−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Immobilization creates a more stable environment which cannot easily be affected by the change in dilution rate . The use of smaller bioreactors in comparison with the fermentation by suspended cell culture systems would reduce capital costs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immobilization creates a more stable environment which cannot easily be affected by the change in dilution rate . The use of smaller bioreactors in comparison with the fermentation by suspended cell culture systems would reduce capital costs …”
Section: Resultsmentioning
confidence: 99%
“…The use of glass beads and glass rushing rings provided productivities of 6 g/(L · h) . Gungormusler et al also reported the benefits of the continuous production of 1,3‐PD from biodiesel derived waste glycerol with cells of K. pneumoniae using ceramic based cell immobilization. The immobilized system presented productivities as high as 10 g/(L · h), two‐fold higher than that reached with suspended cells.…”
Section: Resultsmentioning
confidence: 99%
“…Benefits conferred by cell immobilization might include increased stability in unfavorable environmental conditions during operation as well as avoiding washout [33,131,132]. For example, with microencapsulation, the biomass of K. pneumoniae was increased 2.6-fold compared to free cell cultures [33].…”
Section: Fermentationmentioning
confidence: 99%
“…; Gungormusler et al . ). Recently, the production of biodiesel has lead to the increased availability of crude glycerol (Lee et al .…”
Section: Introductionmentioning
confidence: 97%
“…Klebsiella pneumoniae has been the focus of industrial applications for many years, especially for the production of 1,3-propanediol (1,3-PD) from glycerol (Biebl et al 1999;Gungormusler et al 2011). Recently, the production of biodiesel has lead to the increased availability of crude glycerol (Lee et al 2015;Tchakouteu et al 2015).…”
Section: Introductionmentioning
confidence: 99%